Efficient long-wave infrared ZGP optical parametric oscillator pumped by a diode-pumped AO Q-switched Ho:YAG laser - Hou, Zuoxun; Yang, Song; Zheng, Guoxian (Frontiers in Physics, 2024)
We describe an efficient long-wave infrared optical parametric oscillator based on ZGP crystal pumped by a diode-pumped AO Q-switched Ho:YAG laser in this paper. The wavelength of the laser pulse generated by Ho:YAG laser is 2.09-μm, and the maximum output average power is 25.3 W at repetition rate of 10 kHz. When pumped by such Ho:YAG laser, the maximum average output power of 0.66 W at 9.8 μm is achieved, corresponding to slope efficiency of 5.0% and optical efficiency of 2.6%. Furthermore, the beam quality factor of the long-wave infrared beam is measured to be approximately 1.3. To the authors' best knowledge, this is the best performance reported for a longwave infrared ZGP-OPO pumped by a diode-pumped AO Q-switched Ho:YAG laser.